2013
DOI: 10.3390/ph6121451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oils on Pathogenic Bacteria

Abstract: The increasing resistance of microorganisms to conventional chemicals and drugs is a serious and evident worldwide problem that has prompted research into the identification of new biocides with broad activity. Plants and their derivatives, such as essential oils, are often used in folk medicine. In nature, essential oils play an important role in the protection of plants. Essential oils contain a wide variety of secondary metabolites that are capable of inhibiting or slowing the growth of bacteria, yeasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
1,198
2
55

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,557 publications
(1,299 citation statements)
references
References 137 publications
(211 reference statements)
44
1,198
2
55
Order By: Relevance
“…It is then that medicinal oils extracted from a variety of plants were first recorded as the treatment for various human maladies [1,2]. Today, antibiotics, synthetically produced or naturally occurring chemicals, are amongst the most commonly prescribed drugs in the world, effective in treating pathogenic bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is then that medicinal oils extracted from a variety of plants were first recorded as the treatment for various human maladies [1,2]. Today, antibiotics, synthetically produced or naturally occurring chemicals, are amongst the most commonly prescribed drugs in the world, effective in treating pathogenic bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa infections are most effectively treated with aminoglycosides including amikacin, gentamicin, streptomycin, tobramycin and neomycin which interfere with the 30S subunit during protein synthesis in the bacterium. However, P. aeruginosa has shown an increase in resistance to these once most effective antibiotics [1,6,8,10]. Physicians are running out of antibiotics to treat these serious multi-drug resistant bacterial infections, particularly those caused by gram-negative bacteria like P. aeruginosa [3,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of antibacterial activity of carvone is not completely understood in great detail. It has been demonstrated that the mechanism of action of carvone on the growth of microorganisms includes the destabilization of the phospholipid bilayer structure, interaction with membrane enzymes and proteins, 6 it act as a proton exchanger reducing the pH gradient across the membrane 6,37 and probably it could act by disrupting the metabolic energy state of the cells. In contrast, another study found that carvone was ineffective against the outer membrane of E. coli and S. typhimurium and did not affect their intracellular ATP pool.…”
Section: Resultsmentioning
confidence: 99%